Integrating Python with Leading Computer Forensics Platforms. - Hosmer, Chet.; ScienceDirect eBooks (Cambridge, MA : Syngress is an imprint of Elsevier, 2017)
Integrating Python with Leading Computer Forensic Platforms takes a definitive look at how and why the integration of Python advances the field of digital forensics. In addition, the book includes practical, never seen Python examples that can be immediately put to use. Noted author Chet Hosmer demonstrates how to extend four key Forensic Platforms using Python, including EnCase by Guidance Software, MPE+ by AccessData, The Open Source Autopsy/SleuthKit by Brian Carrier and WetStone Technologies, and Live Acquisition and Triage Tool US-LATT. This book is for practitioners, forensic investigators, educators, students, private investigators, or anyone advancing digital forensics for investigating cybercrime. Additionally, the open source availability of the examples allows for sharing and growth within the industry. This book is the first to provide details on how to directly integrate Python into key forensic platforms.
Print version record.
Elsevier
Keywords: Computer crimes -- Investigation; Python (Computer program language); BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Computer crimes -- Investigation; Python (Computer program language); Electronic books